2018
DOI: 10.1504/ijfip.2018.095859
|View full text |Cite
|
Sign up to set email alerts
|

The influence of business and political ties on supplier selection decisions: the case of the Nigerian public sector

Abstract: Extant relevant literature suggests that nonmarket elements such as social ties are important strategic options that may help organisations enhance their competitiveness relative to other competitors when bidding for important supply jobs. However, our current understanding of their effects on organisational outcomes, especially in public supplier selection decisions in emerging economies, is far from complete. Using a sample of 342 experienced senior management team (SMT) members and senior level staff in 40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 41 publications
(118 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, the non-significant relationship between social ties and performance may imply that the width and depth of the personal connections maintained by decision makers in public sector organizations does not necessarily translate to higher performance; these connections will only be meaningful to performance if they lead to the selection of the ‗right' suppliers. This conclusion is largely consistent with previous studies that found that social ties are important determinants of organizational behavior (Essien et al, 2018), and they may influence organizational outcomes indirectly via appointments to decision making roles and level of resource allocation (Li et al, 2008;Peng & Luo, 2000;Sheng et al, 2011).…”
Section: Discussion -Conclusion and Implicationssupporting
confidence: 92%
See 3 more Smart Citations
“…On the other hand, the non-significant relationship between social ties and performance may imply that the width and depth of the personal connections maintained by decision makers in public sector organizations does not necessarily translate to higher performance; these connections will only be meaningful to performance if they lead to the selection of the ‗right' suppliers. This conclusion is largely consistent with previous studies that found that social ties are important determinants of organizational behavior (Essien et al, 2018), and they may influence organizational outcomes indirectly via appointments to decision making roles and level of resource allocation (Li et al, 2008;Peng & Luo, 2000;Sheng et al, 2011).…”
Section: Discussion -Conclusion and Implicationssupporting
confidence: 92%
“…This makes some sense because it fits into the avoidance strategy often associated with polychronic people (Arndt et al, 2006;Bluedorn et al, 1999;Kaufman-Scarborough & Lindquist, 1999). Moreover, it has been shown that decision makers leverage on their network of political connections to mitigate hostility from the business environment (Essien et al, 2018;Peng & Luo, 2000). Based on the foregoing reasoning, we hypothesise that: H 3 : Social ties will be Significantly Associated with Supplier Selection Decisions.…”
Section: Social Tiesmentioning
confidence: 92%
See 2 more Smart Citations
“…business and political ties) in enhancing supply chain management has received growing but relatively limited attention (see Table 1). It has been documented that managerial ties can have a positive influence on strategic (Essien et al, 2018) and market-based supplier selection (Yan and Lu, 2018). They also can reduce supplier opportunism (Zhu et al, 2017) and promote information sharing (Wang et al, 2014) and specific knowledge acquisition in the buyer-supplier relationship (Zhou et al, 2014).…”
Section: Theoretical Background 21 Managerial Ties: Business and Poli...mentioning
confidence: 99%